Gel electrolyte precursor, electrolyte, semi-solid-state battery and preparation method of semi-solid-state battery

By embedding high phosphorus nitrogen content compounds in gel electrolytes, a highly cross-linked interpenetrating network is solved, and the safety challenges and cycle stability problems of existing semi-solid lithium-ion batteries in high specific energy and large capacity battery cells are achieved, and efficient flame retardant and stable battery performance are achieved.

CN119890429APending Publication Date: 2025-04-25WANXIANG 123 CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510055185.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing semi-solid lithium-ion batteries have safety challenges in high-specific energy, large-capacity battery cells. The introduction of flame retardant may affect the ionic conductance of the electrolyte and the formation of the negative electrode interface layer, reducing the cycling stability of the battery.

Method used

A high-phosphorus nitrogen content compound with high-efficiency flame retardant properties is used as the gel electrolyte precursor, and it is embedded in the polymer segment through in-situ polymerization to build a highly cross-linked interpenetrating network to improve the flame retardant efficiency and cyclic stability of the electrolyte.

Benefits of technology

The efficient embedding of high phosphorus nitrogen content compounds in gel electrolytes is achieved, the flame retardant efficiency and cycle stability of lithium-ion batteries are improved, and the negative impact of flame retardant on the conductivity and SEI film is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005241199790000021
    Figure BDA0005241199790000021
  • Figure BDA0005241199790000022
    Figure BDA0005241199790000022
  • Figure BDA0005241199790000051
    Figure BDA0005241199790000051
Patent Text Reader

Abstract

The invention discloses a gel electrolyte precursor, an electrolyte, a semi-solid battery and a preparation method of the gel electrolyte precursor, and belongs to the technical field of lithium ion batteries. According to the gel electrolyte precursor provided by the invention, a large number of high-phosphorus-nitrogen-content compounds with efficient flame-retardant performance are embedded into polymer chain segments by utilizing an in-situ polymerization method, so that the high-phosphorus-nitrogen-content compounds with high-efficiency flame-retardant performance are formed; meanwhile, a polymer highly-crosslinked interpenetrating network is constructed by utilizing the multi-substitution characteristic of the molecular structure. According to the structural design, the problem of low flame-retardant efficiency of a polymerization type flame-retardant electrolyte is solved, and the problem that an additive type flame-retardant electrolyte affects ionic conductivity and SEI film production is also avoided. On the other hand, the Young modulus and the strength of the gel electrolyte are improved by the highly crosslinked polymer structure, so that the cycling stability and the lithium dendrite resistance of the lithium ion battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to lithium ion battery technology, and in particular to a gel electrolyte precursor, an electrolyte, a semi-solid battery and a preparation method thereof. Background Art

[0002] Using solid electrolytes to replace organic liquid electrolytes has fundamentally solved the safety problems of traditional lithium batteries such as thermal runaway and leakage, and has become an inevitable path to solve battery safety problems. However, the current solid-state battery technology has the following problems: the performance of various solid electrolyte materials has distinct advantages and disadvantages, making it difficult to take into account the various needs of commercial applications; the engineering path is unclear, and large-scale manufacturing is difficult; and the material and manufacturing costs are high. In response to the above problems, by introducing polymer or oxide solid electrolytes into the electrolyte components and reducing the liquid content, a semi-solid battery that takes into account both safety and battery kinetic performance is formed. From the perspective of implementation difficulty and existing production capacity utilization, it is expected to become an important starting point for the recent iteration of high-safety lithium battery technology.

[0003] At present, the implementation route for semi-solid batteries in the industry has become clearer, mainly focusing on gel electrolyte materials, developing in-situ curing technology, and achieving great compatibility with existing battery production processes. Compared with traditional liquid electrolytes, this gel electrolyte retains a higher ionic conductivity, and the in-situ curing technology solves the contact problem with the electrode interface. At the same time, constrained by the polymer network, the fluidity of the flammable components in the battery is reduced, the flash point is increased, and the internal short circuit tolerance is improved to a certain extent, thereby improving the safety of the battery. However, since there is still a considerable amount of flammable components in the gel electrolyte, the heat accumulation after the battery loses control is still huge. Therefore, this technology is not enough to fully cope with the safety challenges of high specific energy and large-capacity batteries.

[0004] In view of the above problems, a simple and feasible technical solution is to introduce flame retardants to improve the thermal stability of gel electrolytes. According to the type of materials, common flame retardants include halogens, phosphorus-containing compounds, nitrogen-containing compounds, inorganic silicon-based materials, MOFs, graphene, etc.

[0005] Patent CN202010156622.9 relates to a semi-interpenetrating network flame-retardant gel electrolyte, a lithium-ion battery and a preparation method. After blending a fluorine-containing organic reagent, a lithium salt, a cross-linking agent, a polymerization monomer and an initiator, an in-situ polymerization is used to prepare a semi-interpenetrating network flame-retardant gel electrolyte. The introduction of fluorine into the electrolyte can more effectively form a solid electrolyte interphase and a positive electrode electrolyte interphase, thereby improving the thermal and electrochemical stability of the battery. Fluorides are generally not easy to burn, which can improve the safety of the battery.

[0006] However, although the introduction of one or more flame retardants into the gel electrolyte system in the form of solvents or additives is more tolerant to the choice of flame retardants, the introduction method is simple and easy to operate, and it is convenient for large-scale preparation. However, most flame retardants are not conducive to the dissociation of lithium salts, affecting the ion conductivity of the electrolyte, thereby increasing the internal resistance. More importantly, the addition of flame retardants is often not conducive to the formation of the negative electrode solid electrolyte interface layer (SEI), resulting in continuous reaction of the electrolyte at the negative electrode interface, reducing the battery cycle stability.

[0007] Patent CN202111632648.7 provides a gel polymer electrolyte with gas-phase flame retardant function and a battery, wherein the matrix of the polymer electrolyte is formed by homopolymerization of monomers of non-combustible or flame-retardant substances with gas-phase flame retardant function or copolymerization with a first monomer. Under high temperature conditions (120-300°C), a condensation reaction will occur rapidly to produce a large amount of non-combustible or flame-retardant volatiles, thereby reducing the concentration of combustible gas to below the lower combustion limit; at the same time, the concentration of oxygen in the combustion zone is diluted to prevent the continuation of combustion. The condensation reaction between polymer matrices is an endothermic reaction, and the thermosetting high-density cross-linked polymer network formed at the same time has the function of isolating heat and oxygen, which synergistically inhibits combustion.

[0008] The above method connects the flame retardant species originally dispersed in the electrolyte to the gel electrolyte polymer skeleton through polymerization reaction or cross-linking reaction of polymer monomers with flame retardant function, thereby reducing the influence of these species on the negative electrode film formation. However, this method has high requirements for the design of inhibitor molecules, mainly unsaturated alkane phosphates. Due to the limitation of species selection, these methods have low flame retardant efficiency and have limited improvement on the safety performance of lithium-ion batteries. Summary of the invention

[0009] The object of the present invention is to provide a gel electrolyte precursor with flame retardant function; another object of the present invention is to provide a gel electrolyte with flame retardant function; another object of the present invention is to provide a gel semi-solid battery with flame retardant function and good cycle performance.

[0010] The present invention discloses a gel electrolyte precursor. The raw materials of the gel electrolyte precursor include, by weight:

[0011]

[0012] The first monomer comprises a compound having structural formula (I):

[0013]

[0014] Among them, R1-R6 are substituents containing unsaturated olefins, halogenated groups, phenoxy derivative groups, amino derivative groups, pyridine derivative groups or pyrrole derivative groups; the chain length of the substituents in R1-R6 does not exceed 12 carbon atoms; and R1-R6 include at least 3 identical substituents containing unsaturated olefins.

[0015] The first monomer has at least three unsaturated olefin substituents and has good cross-linking performance; at the same time, the first monomer has high phosphorus and nitrogen high-efficiency flame retardant performance, so that the first monomer has flame retardant cross-linking function.

[0016] Furthermore, the substituent containing unsaturated olefin is oxystyryl, phenoxypropylene, phenoxyacrylic acid, N-pyridylvinyl or styrene boric anhydride.

[0017] The preparation method of the first monomer is: adding a phenol derivative containing an unsaturated olefin group and an alkaline substance into a solvent and stirring for 4-24 hours to prepare a phenol derivative sodium salt solution;

[0018] Dissolve hexachlorocyclotriphosphazene in a solvent to form a uniform solution, control the temperature of the hexachlorocyclotriphosphazene solution at 0-5°C, add the phenol derivative sodium salt solution dropwise with stirring in a protective gas atmosphere, then raise the temperature to 50-70°C, and continue stirring for 4-24 hours; filter and rotary evaporate to remove the solvent to obtain a viscous substance, wash with water, recrystallize, and vacuum dry to obtain the first monomer.

[0019] The phenol derivative containing an unsaturated olefin group is preferably vinylphenol, propenylphenol, hydroxyphenyl acrylate, etc., the alkaline compound is preferably sodium hydroxide, potassium hydroxide, etc., and the solvent is preferably tetrahydrofuran, acetone and N,N-dimethylformamide.

[0020] Furthermore, the second monomer is n-pentene, acrylic acid, acrylic ester, acrylonitrile, acrylamide, styrene, butadiene, isoprene, maleic anhydride or methyl methacrylate.

[0021] Further, the initiator includes any one of dibenzoyl peroxide, dicyclohexyl peroxydicarbonate, tert-butyl peroxy-2-ethylhexanoate, azobisisoheptylonitrile, and azobisisobutyronitrile, or a combination of at least two thereof.

[0022] Furthermore, the organic solvent includes any one of linear or cyclic carbonates and fluorinated carbonates, or a combination of at least two of them.

[0023] The lithium salt includes any one of LiPF6, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, lithium bis(oxalate)borate, LiBF4, and LiClO4, or a combination of at least two thereof.

[0024] Furthermore, the electrolyte additive includes any one of vinylene carbonate, fluoroethylene carbonate, and ethylene sulfate, or a combination of at least two thereof.

[0025] The invention also discloses a gel electrolyte, which is prepared by uniformly mixing the raw materials of the gel electrolyte precursor mentioned above and performing gelation.

[0026] The present invention also discloses a method for preparing a gel semi-solid battery. Under environmental conditions where the moisture and oxygen content is controlled to be ≤10ppm, the raw materials of the gel electrolyte precursor as described above are mixed evenly, injected into an assembled dry battery cell, and packaged; the battery cell after liquid injection is placed and subjected to gelation treatment so that the gel electrolyte precursor forms a gel electrolyte between the positive electrode and the negative electrode; the gelled gel battery cell is placed under a pressure of 2-60psi, and subjected to pre-charging, formation, and capacity separation to obtain a gel semi-solid battery.

[0027] Furthermore, the battery cell after injection is placed under the following conditions: standing at room temperature for 12-48 hours.

[0028] The battery cell injected with the gel precursor is left to stand at room temperature for 12-48 hours to allow the gel precursor to fully infiltrate the positive and negative electrode plates.

[0029] Furthermore, the gelation treatment conditions are: placing under a pressure of 2-60 psi, a temperature of 35-70° C., and standing for 12-96 hours.

[0030] The invention also discloses a gel semi-solid battery, which is prepared by the preparation method described above.

[0031] The gel electrolyte precursor provided by the present invention uses an in-situ polymerization method to embed a large amount of high phosphorus-nitrogen content compounds with efficient flame retardant properties into polymer segments, and at the same time uses the multi-substitution characteristics of its molecular structure to construct a highly cross-linked interpenetrating polymer network. Such a structural design solves the problem of low flame retardant efficiency of polymeric flame retardant electrolytes, and avoids the problem of additive flame retardant electrolytes affecting ionic conductivity and SEI film production. On the other hand, the highly cross-linked polymer structure improves the Young's modulus and strength of the gel electrolyte, thereby improving the cycle stability and resistance to lithium dendrites of lithium-ion batteries. DETAILED DESCRIPTION

[0032] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments.

[0033] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. All reagents or instruments without manufacturer specified are conventional products that can be purchased through regular channels.

[0034] Example 1

[0035] The first monomer hexa(oxy-p-phenylene)polycyclotriphosphazene is prepared, and its structural formula is as follows:

[0036]

[0037] Add 3.44 g of NaOH to a three-necked flask, then add 100 ml of tetrahydrofuran, and introduce nitrogen for 5 minutes. Then weigh 12.96 g of 4-vinylphenol and slowly drop it into the three-necked flask. Transfer the flask to a constant temperature oil bath and stir at 50°C for 12 hours until the reaction is complete to obtain a tetrahydrofuran solution of 4-vinylphenol sodium salt.

[0038] Dissolve 5g of hexachlorocyclotriphosphazene in 50ml of tetrahydrofuran to form a uniform solution. Place the tetrahydrofuran solution of hexachlorocyclotriphosphazene in an ice bath to control the temperature at 0-5°C, and introduce nitrogen for 5 minutes. Add the prepared tetrahydrofuran solution of 4-vinylphenol sodium salt dropwise under stirring. After the system temperature is cooled to below 20°C, transfer the three-necked flask to a constant temperature oil bath pot and continue stirring at 50°C for 24 hours. Filter and evaporate the tetrahydrofuran to obtain a yellow viscous substance, wash with deionized water, then recrystallize and vacuum dry to obtain the first monomer hexa(oxy-p-phenylethylene)polycyclotriphosphazene.

[0039] Preparation of gel semi-solid battery:

[0040] Under the condition that the moisture and oxygen content are ≤10ppm, 5g of hexa(oxy-p-phenylene)polycyclotriphosphazene, 3g of methyl methacrylate, 30mg of azobisisobutyronitrile, 12g of lithium bis(trifluoromethylsulfonyl)imide, 75g of a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (mass ratio of 3:7) and 2.7g of vinylene carbonate acrylate are mixed to obtain a mixture A;

[0041] Under the same environmental conditions, mixture A was added to a 6Ah soft-pack dry battery cell (high-nickel ternary NCM811 / / silicon oxide (SiOx) / graphite (Gr) chemical system), and after rapid packaging, the cell was placed at room temperature for 24 hours. The cell was then placed in an environment of 10psi pressure and 45°C for 48 hours to allow the electrolyte precursor to fully solidify. After the solidified cell was cooled, pre-charging, formation, and capacity separation were completed to obtain a gel semi-solid battery.

[0042] Example 2

[0043] The first monomer tris(4-allylphenoxy), trichloropolycyclotriphosphazene is prepared, and its structural formula is as follows:

[0044]

[0045] Add 3.44 g of NaOH to a three-necked flask, then add 200 ml of tetrahydrofuran, and introduce nitrogen for 5 min. Then weigh 12.96 g of 4-isopropenylphenol and slowly dropwise add it to the three-necked flask. Transfer the flask to a constant temperature oil bath and stir at 50°C for 12 hours until the reaction is complete to obtain a tetrahydrofuran solution of 4-isopropenylphenol sodium salt.

[0046] Dissolve 5g of hexachlorocyclotriphosphazene in 50ml of tetrahydrofuran to form a uniform solution. Place the tetrahydrofuran solution of hexachlorocyclotriphosphazene in an ice bath to control the temperature at 0-5°C, and introduce nitrogen for 5 minutes. Add the prepared tetrahydrofuran solution of 4-isopropenylphenol sodium salt dropwise under stirring. After the system temperature cools to below 20°C, transfer the three-necked flask to a constant temperature oil bath and continue stirring at 50°C for 24 hours. After filtering and removing tetrahydrofuran by rotary evaporation, a yellow viscous substance is obtained, which is washed with deionized water, then recrystallized and vacuum dried to obtain the first monomer tris(4-allylphenoxy), trichloropolycyclotriphosphazene.

[0047] The difference between Example 2 and Example 1 is that the first monomer hexa(oxy-p-phenylene)polycyclotriphosphazene is replaced with tri(4-allylphenoxy)trichloropolycyclotriphosphazene.

[0048] Example 3

[0049] The difference between Example 3 and Example 1 is that in step 1, the second monomer methyl methacrylate is replaced with acrylic acid.

[0050] Comparative Example 1

[0051] The difference between Comparative Example 1 and Example 1 is that the hexa(oxy-p-phenylethylene)polycyclotriphosphazene in step 3 is replaced by diethyl allyl phosphate.

[0052] Comparative Example 2

[0053] The difference between Comparative Example 1 and Example 1 is that the hexa(oxy-p-phenylethylene)polycyclotriphosphazene in step 3 is replaced with trimethylolpropane trimethacrylate, and the amount of the mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (mass ratio of 3:7) added is changed to 70 g, and 5 g of hexachloropolycyclotriphosphazene is additionally added.

[0054] Performance Testing:

[0055] The self-extinguishing time after the gel electrolyte in Examples 1-3 and Comparative Examples 1-2 was fully ignited (maintained in a flame for 10 seconds) and the room temperature cycling performance of the battery were tested. The cycling test temperature was 25°C, with a 1C / 1C charge and discharge rate and a 100% charge and discharge depth. The results are shown in Table 1 below.

[0056] Table 1 Test results

[0057] experiment Extinguishing time / s Capacity retention rate @500 cycles / % Example 1 2 87 Example 2 2 84 Example 3 3 86 Comparative Example 1 16 83 Comparative Example 2 7 76

[0058] As shown in Table 1, compared with Comparative Example 1, Examples 1-3 show that the gel electrolyte with flame retardant function provided by the present invention can effectively improve the flame retardant efficiency; compared with Comparative Example 2, the results of Examples 1-3 show that the polymerized flame retardant component can effectively improve the effect of the flame retardant on the battery cycle performance compared with the added flame retardant component.

[0059] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A gel electrolyte precursor, characterized in that: The raw materials of the gel electrolyte precursor include, by weight: The first monomer comprises a compound having structural formula (I): Among them, R1-R6 are substituents containing unsaturated olefins, halogenated groups, phenoxy derivative groups, amino derivative groups, pyridine derivative groups or pyrrole derivative groups; the chain length of the substituents in R1-R6 does not exceed 12 carbon atoms; and R1-R6 include at least 3 identical substituents containing unsaturated olefins.

2. The gel electrolyte precursor according to claim 1, characterized in that: The substituent containing unsaturated olefin is oxystyryl, phenoxypropylene, phenoxyacrylic acid, N-pyridylvinyl or styrene boric anhydride.

3. The gel electrolyte precursor according to claim 1, characterized in that: The second monomer is n-pentene, acrylic acid, acrylic ester, acrylonitrile, acrylamide, styrene, butadiene, isoprene, maleic anhydride or methyl methacrylate.

4. The gel electrolyte precursor according to claim 1, characterized in that: The initiator includes any one of dibenzoyl peroxide, dicyclohexyl peroxydicarbonate, tert-butyl peroxy-2-ethylhexanoate, azobisisoheptylonitrile, and azobisisobutyronitrile, or a combination of at least two thereof.

5. The gel electrolyte precursor according to claim 1, characterized in that: The organic solvent includes any one of linear or cyclic carbonates and fluorinated carbonates, or a combination of at least two of them.

6. The gel electrolyte precursor according to claim 1, characterized in that: The electrolyte additive includes any one of vinylene carbonate, fluoroethylene carbonate, and ethylene sulfate, or a combination of at least two thereof.

7. A gel electrolyte, characterized in that: The gel electrolyte precursor is prepared by uniformly mixing the raw materials of any one of claims 1 to 6 and performing gelation.

8. A method for preparing a gel semi-solid battery, characterized in that: The following steps are involved: Under the environmental condition of controlling the moisture and oxygen content to be ≤10ppm, the raw materials of the gel electrolyte precursor as claimed in any one of claims 1 to 6 are mixed evenly, injected into the assembled dry battery cell, and packaged; Placing the injected battery cell and subjecting it to gelation treatment, so that the gel electrolyte precursor forms a gel electrolyte between the positive electrode and the negative electrode; The gelled gel cell is placed under a pressure of 2-60 psi, and subjected to pre-charging, formation and capacity division to obtain a gel semi-solid battery with flame retardant function.

9. The method for preparing a gel semi-solid battery according to claim 8, characterized in that: The battery cell after injection is placed under the following conditions: standing at room temperature for 12-48 hours; the gelation treatment conditions are: placed at a pressure of 2-60 psi and a temperature of 35-70° C. for 12-96 hours.

10. A gel semi-solid battery, characterized in that: The preparation is obtained by the preparation method as claimed in claim 8 or 9.

Citation Information

Patent Citations

  • A semi-interpenetrating network flame-retardant gel electrolyte, a lithium-ion battery, and its preparation method

    CN111224156B

  • Polymer electrolyte with gas-phase flame-retardant function and battery

    CN114373990A